Mechanism and therapeutic targets of circulating immune cells in diabetic retinopathy - Bowen Zhao; Yin Zhao; Xufang Sun (Elsevier, 2024)
Diabetic retinopathy (DR) continues to be the leading cause of preventable vision loss among working-aged adults, marked by immune dysregulation within the retinal microenvironment. Typically, the retina is considered as an immune-privileged organ, where circulating immune cells are restricted from entry under normal conditions. However, during the progression of DR, this immune privilege is compromised as circulating immune cells breach the barrier and infiltrate the retina. Increasing evidence suggests that vascular and neuronal degeneration in DR is largely driven by the infiltration of immune cells, particularly neutrophils, monocyte-derived macrophages, and lymphocytes. This review delves into the mechanisms and therapeutic targets associated with these immune cell populations in DR, offering a promising and innovative approach to managing the disease.